Integration of auditory and vibrotactile stimuli: Effects of frequency - Wilson, E. Courtenay (Acoustical Society of America, 2010)
Perceptual integration of vibrotactile and auditory sinusoidal tone pulses was studied in detection experiments as a function of stimulation frequency. Vibrotactile stimuli were delivered through a single channel vibrator to the left middle fingertip. Auditory stimuli were presented diotically through headphones in a background of 50 dB sound pressure level broadband noise. Detection performance for combined auditory-tactile presentations was measured using stimulus levels that yielded 63% to 77% correct unimodal performance. In Experiment 1, the vibrotactile stimulus was 250 Hz and the auditory stimulus varied between 125 and 2000 Hz. In Experiment 2, the auditory stimulus was 250 Hz and the tactile stimulus varied between 50 and 400 Hz. In Experiment 3, the auditory and tactile stimuli were always equal in frequency and ranged from 50 to 400 Hz. The highest rates of detection for the combined-modality stimulus were obtained when stimulating frequencies in the two modalities were equal or closely spaced (and within the Pacinian range). Combined-modality detection for closely spaced frequencies was generally consistent with an algebraic sum model of perceptual integration; wider-frequency spacings were generally better fit by a Pythagorean sum model. Thus, perceptual integration of auditory and tactile stimuli at near-threshold levels appears to depend both on absolute frequency and relative frequency of stimulation within each modality.